Exploring Professional Development Practices: Insights from Gurukul, Sanskrit, and General Schools - Basnet, Bhavana; Bhantana, Kamala (Marsyangdi Journal, 2024)
This study aims to examine the professional development strategies used by teachers in Gurukul, Sanskrit, and general schools in Karnali and Gandaki provinces. The purpose of the study is to gain insight into the strategies teachers employ to advance their professional development. Through focus group discussions with a purposeful sample of six teachers, the study investigated the variety of professional development strategies used in these institutions. The study's findings revealed that teachers employ numerous strategies, including professional development training, field trips, peer collaboration, workshops, seminars, sharing of best practices, and technology integration. In addition, the study considered cultural norms, infrastructure constraints, and regional challenges as contextual factors that influence the implementation and efficacy of professional development strategies.